Feeding site of the spittlebug Mahanarva fimbriolata (Stål) (Hemiptera: Cercopidae) on sugarcane (Scientia Agricola, 2007)
The sugarcane spittlebug Mahanarva fimbriolata (Stål) (Hemiptera: Cercopidae) is a pest of mechanically-harvested sugarcane in Brazil, when trash burning is not performed. To better understand the differences in feeding behavior of adults and nymphs of this pest and the subsequent disorders that arise, stylet penetration through fixation, staining and sectioning was investigated. Nymphs cause a "physiological disorder" damaging the tracheary system of the roots, slowing or preventing water and nutrient flow, with phloem and xylem dehydration. Nymphs insert their stylets through the epidermis, crossing the cortex, endodermis and pericycle before reaching the vascular cylinder, where they feed in the sieve-tube elements of the primary phloem. In contrast, adults feed on leaves, causing "sugarcane burn", and reducing plant photosynthesis. Adults introduce the stylets into the leaf blade through the stomata, passing the chlorophyll-bearing parenchyma cells before reaching the metaxylem in the vascular bundles.